2018
DOI: 10.21037/jtd.2018.03.45
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of multimodality therapy for esophageal cancer with distant metastasis

Abstract: Background: The purpose of this study is to evaluate outcomes in upfront local response and survival of patients with esophageal cancer and distant metastasis. Methods: This retrospective study included 34 patients (25 males) aged 42-92 years (median, 70 years) with a histological diagnosis of esophageal squamous cell cancer with distant metastasis. Staging was performed according to the UICC's TNM (6th edition) classification of malignant tumor. Results:The median survival time (MST) was 5 months. The 1-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Metastatic ESCC patients had a poor prognosis, and the 5-year survival rate was no more than 5% ( 7 ). LAT to the primary or metastatic sites may be suitable choices that not only relieve symptoms to improve life quality but also prolong the survival time in metastatic ESCC patients ( 18 21 ). However, previous studies were mostly retrospective studies with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metastatic ESCC patients had a poor prognosis, and the 5-year survival rate was no more than 5% ( 7 ). LAT to the primary or metastatic sites may be suitable choices that not only relieve symptoms to improve life quality but also prolong the survival time in metastatic ESCC patients ( 18 21 ). However, previous studies were mostly retrospective studies with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The radiation dose of palliative intent for metastatic EC reportedly ranges from 30 to 50 Gy ( 21 23 ). However, a higher radiation dose with a definitive aim appears to produce better survival outcomes in metastatic EC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these results are compared to previous results for esophageal cancer, our cohort showed longer survival. Actually, it has been reported that MSTs of patients with metastatic esophageal cancer were around 5 to 21 months (17)(18)(19)(20). Regarding recurrence after curative surgery for esophageal cancer, survival of patients with distant metastasis was worse than that of patients with locoregional recurrence (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…During later stages of the disease, patients may experience obstruction or dysphagia, but successful or curative treatment may be impossible at these stages. Complete surgical resection may be too difficult, and chemotherapy and radiotherapy may be insufficient after tumors have metastasized [7]. Research is needed to identify curative treatments for patients with esophageal squamous cell carcinoma (ESSC) and EADC.…”
Section: Introductionmentioning
confidence: 99%